1991
DOI: 10.1093/carcin/12.8.1465
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of acetyltransferase activities in the intestines of rapid and slow acetylator rabbits

Abstract: Epidemiological studies have shown that there is a significantly greater proportion of the rapid acetylator phenotype in patients with colorectal tumors than in controls; phenotype-related differences in bioactivation of dietary or environmental amines in the intestinal epithelium have been suggested as a mechanism for this effect. In the present study, we have used hepatic and intestinal cytosols to compare N-acetyltransferase (NAT1 and NAT2), O-acetyltransferase (OAT) and arylhydroxamic acid N,O-acyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This is consistent with previous studies reporting a general decrease in NAT2 activity along the gastrointestinal tract in rabbits [21], Syrian hamsters [38], and humans [25]. Although SMZ N-acetyltransferase activity (NAT1) was highest in liver, it was detected in all tissues tested except for prostate and heart.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies reporting a general decrease in NAT2 activity along the gastrointestinal tract in rabbits [21], Syrian hamsters [38], and humans [25]. Although SMZ N-acetyltransferase activity (NAT1) was highest in liver, it was detected in all tissues tested except for prostate and heart.…”
Section: Discussionsupporting
confidence: 92%
“…However, the relative expression of the arylamine NAT1 and NAT2 isozymes may differ in human colons. For example, recent studies in the rabbit have reported that NAT2 is primarily expressed in the upper intestinal tract (duodenum and jejunum) with little or none present in the large intestine (Ilett et al 1991;Reeves et al 1992). In contrast, NAT1 expression was uniformly high along the rabbit intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis derives from studies in the rabbit model where N-acetyltransferase activities reflected the NAT2 genetic polymorphism in the liver and gut, but not in other tissue cytosols, suggesting either absence or a much smaller contribution of rabbit NAT2 in these other tissues (Hearse and Weber, 1973). Furthermore, a subsequent study reported that the rapid/slow NAT2 ratio for both sulfamethazine Nacetyltransferase and N-hydroxy-ABP O-acetyltransferase activities were much higher in rabbit liver than small and large intestine (Ilett et al, 1991). Thus, these studies in rabbit suggested that NAT2 genotype-dependent differences are expressed primarily in the liver and to a lesser extent in the gastrointestinal tract, and therefore suggest that NAT2 genotype-dependent differences in carcinogenesis following exposures to carcinogens primarily reflect NAT2 genotype-dependent hepatic versus extrahepatic metabolism of the carcinogen and/or its metabolites.…”
Section: Phenotypic Expression Of the Nat2 Polymorphismmentioning
confidence: 99%